The secular and the sacred: reflections on Charles Taylor's A Secular Age. Issue 1 (2nd January 2016) - Mellon, James G.
ABSTRACT: Charles Taylor's A Secular Age represents a remarkable achievement. Taylor insists in a reasoned way that the sacred continues to have an important and legitimate role, and challenges assumptions, whether based on Weberian or Durkheimian understandings of religion in society, that faith no longer has a place. In doing this, he distinguishes among different aspects of the secularisation thesis. In this article I assert that there is a coherence to Taylor's body of work, including A Secular Age, and I trace certain themes, such as a concern with notions of the self, that run through his work. I also identify in Taylor's argument links to the thought of thinkers like Blondel, Gilson, Maritain and Marcel, and to the notion of an apologetics of hope.